Angola's incomplete transition - Renato Aguilar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Angola's difficulties in achieving macro-economic stability and economic liberalization have serious implications for private-sector development. Hyperinflation, and frequent policy reversal, constrain and distort investment in both the informal and formal parts of the private sector. But macro-economic instability arises in part out of mechanisms that subsidize powerful oligopolies, enabling them to capture a portion of the large oil rents. These subsidies, together with market controls, enable the oligopolies to profit at the expense of small- and micro-enterprises, thereby hindering the creation of more employment for Angola's poor. Therefore the new private sector that is evolving in Angola owes its character to three factors: the course of the war; the country's natural resource windfall; and the way in which liberalization and privatization have been pursued.
Keywords: O10; O55; 330; Sub-Saharan Africa; Angola; conflict; economic reform; Bürgerkrieg; Kriegsschaden; Wirtschaftsreform; Privatwirtschaft; Angola